Modulation of Neural Activity for Myelination in the Central Nervous System - Choi, Elliot H.; Blasiak, Agata; Lee, Joonho; Yang, In Hong (Frontiers in Neuroscience, 2019)
Electrical stimulation has been playing a significant role in revealing various functions and mechanisms of the nervous system. It is no different for myelination, a process in which oligodendrocytes in the central nervous system (CNS) or Schwann Cells in the peripheral nerve system (PNS) wrap around axons to provide an insulation layer in vitro and in vivo. It has been widely recognized that the myelin sheath accelerates axon signal conduction and provides neuroprotection. Recent studies have begun to reveal its role in plasticity. The major mechanism that enables this process is activity-dependent myelination – the phenomenon where neural activity in neurons supports oligodendrocyte maturation, myelin sheath formation and its wrapping. In light of the recent discoveries, the understanding of this phenomenon has a potential to provide therapeutic targets for not only the demyelination diseases but also psychiatric disorders. There is a growing need for experimental platforms capable of dissecting the effect of neural activity on myelination in health and disease. The effect of neural activity is commonly studied by comparing the myelination levels in cultures with neurons of low and high activity. Electrical stimulation is particularly well suited as a method of inducing neural activity in these systems. In this review we describe in vitro platforms for studying activity dependent myelination that utilize neuron stimulation via electrical field. We discuss stimulation profiles, as well as the alternatives to the electrical stimulation as applied in regular, compartmentalized and organotypic co-cultures.